Longitudinal analyses of the effects of neutralizing antibodies on interferon beta-1b in relapsing-remitting multiple sclerosis. - Petkau, A; White, R; Ebers, G; Reder, A; Sibley, W; Lublin, F; Paty, D (2004)
We have analysed data on exacerbation rates, Expanded Disability Status Scale (EDSS) scores, and lesion burdens using the results of two neutralizing antibody (NAB) assays (CPE and MxA) from the pivotal relapsing-remitting multiple sclerosis (MS) trial of interferon beta-1b (IFNB) with a longitudinal approach, where the influence of NABs in individual patients is assessed by comparing responses during NAB-positive and NAB-negative periods. There are apparent influences on exacerbation rate related to dose of IFNB, titer level, and duration of positivity. With the MxA assay, exacerbation rates after switching to NAB-positive status are estimated to be 28% higher [95% confidence interval (CI): (-15%, 92%)] and -2% higher [95% CI: (-21%, 21%)] on the low- and high-dose IFNB arms, respectively. When compared with all NAB-negative periods, exacerbation rates during NAB-positive periods are estimated to be 29% higher [95% CI: (0%, 67%)] and 18% higher [95% CI: (0%, 40%)] on the low- and high-dose IFNB arms, respectively. When NAB-positive patients again become NAB-negative, no evidence of increased exacerbation rates could then be demonstrated. More detailed exploratory analyses indicate that the effects are most evident in the approximately 20% of patients developing high titers. In these patients, the influence of NABs may be self-limited, as titers often diminish or NABs become undetectable with time.